When Should Definitive Surgery Be Performed After Sacrococcygeal Pilonidal Sinus Abscess Drainage - Güler, Yılmaz; Şengül, Serkan; Çalış, Hasan; Karabulut, Zülfikar; Özen, Özkan (Cerrahpaşa Medical Journal, 2023)
Objectives : The abscess development is one of the common clinical presentations of pilonidal sinus.Treatment in pilonidal sinus abscesses involves allowing secondary recovery following wide local excision with drainage and excision procedures are performed after a few weeks and after the infection is completely cured. We aimed to investigate the effect of the time interval between the abscess drainage and definitive surgical treatment on the development of postoperative complications in patients who had pilonidal sinus abscess. Methods: The patients were divided into two groups according to the time interval from abscess drainage to sinus excision surgery; Patients who underwent sinus excision 1 month after abscess drainage comprised group 1, and patients who underwent sinus excision 3 months after abscess drainage comprised group 2. Sinus excision and primary closure surgery were performed in patients in both groups. Results: 44 patients (53.0%) underwent sinus excision group 1 and 39 patients (47.0%) underwent sinus excision group 2 after abscess drainage. Postoperative wound infection and wound dehiscence rates were significantly higher in group 1 patients than in group 2 patients. (p˂ 0.05) Conclusions: We suggest that for reducing postoperative complications, it would be a better approach performing sinus excision after waiting for at least 3 months following drainage instead of performing excision right after recovery of infection or within a few weeks after the abscess drainage. Cite this article as: Guler Y, Sengul S, Calis H, Karabulut Z, Ozen O. When should definitive surgery be performed after sacrococcygeal pilonidal sinus abscess drainage. Cerrahpaşa Med J. 2023;47(3):274-278.